SYNCHRONIZATION OF ESTRUS WITH PGF ANALOGUE IN EWES AND GOATS DURING TWO SEASONS - H.A.K, AL-SAADI,; H.H., AL-ATTIA, (The Iraqi Journal of Veterinary Medicine, 1989)
Trials had been made for synchronization of estrus in both ewes and goats during Summer and Autumn seasons following double injection of PGF 2α . The results showed that the synchronization of estrus as well as the conception rates in ewes were lower than that of the goats during both seasons.